The correlation among occupational stress, coping style and depressive symptoms in 2083 Chinese manufacturing workers. - Li, Xiaoyi; Chen, Huiqing; Liao, Xiqing; Huang, Manqi; Liu, Xiaoman; Guo, Yao; Chen, Jiabin; Li, Shuang (Work, 2025)
Background: Chinese manufacturing workers have been carrying out repetitive, monotonous and fast-paced operations for a long time, long working hours and maintaining the same working posture, dense assembly lines, crowded working space, etc., resulting in various physical and mental health problems of workers. Objective: This study aims to understand the mental health of Chinese manufacturing workers and investigate the correlation among occupational stress, coping style and depressive symptoms. Methods: A total of 2083 workers from two manufacturing enterprises in Beijing City and four manufacturing enterprises in Guangdong Province are selected as study subjects using judgment sampling method. The occupational stress, coping style, and depression symptoms are accessed using the Core Occupational Stress Measurement Scale, Trait Coping Style Questionnaire and Patient Health Questionnaire Depression Scale, and we analyze the correlation among occupational stress, coping style and depressive symptoms. Results: This is a cross-sectional and correlational study. The sample of the study consisted of 2083 Chinese manufacturing workers. The average scores of occupational stress, positive coping style, negative coping style and depressive symptoms among the study subjects are 45.2, 31.7, 23.7 and 6.3, respectively. The detection rates of occupational stress and depressive symptoms are 29.5% and 15.7%. Depressive symptoms are positively correlated with occupational stress and negative coping style (p < 0.001), and negatively correlated with positive coping style (p < 0.001). Occupational stress is positively correlated with negative coping style (p < 0.001) and negatively correlated with positive coping style (p < 0.001). The four dimensions of occupational stress explained 15.8% of variation in depressive symptoms (p < 0.001). The inclusion of the two dimensions of coping style on the above basis can explain 19.3% of the variation in depressive symptoms (p < 0.001). Meanwhile, the four dimensions of occupational stress has a statistically significant effect on depressive symptoms (p < 0.05). Conclusions: Occupational stress can directly affect the occurrence of depressive symptoms in Chinese manufacturing workers. Coping style moderates the effect of occupational stress on depressive symptoms. Positive coping style can help alleviate the adverse effects of occupational stress and reduce the risk of depressive symptoms.